SYNANTHROPIZATION OF CORVIDS AND THEIR ADAPTATIONS TOWARDS HUMAN TRANSFORMED LANDSCAPES - Matsyura, A. V.; Zimaroyeva, A. A. (Acta Biologica Sibirica, 2016)
The animal meet the special (positive and negative) conditions for the existence within the urban area. Spatial reduction of natural habitats makes animal to move to less suitable habitats, and the lack of conditions for temporary resting places causes the animals to occupy the new ecological niches. Restricting of food resources leads to a transition to the use of atypical foods. In urban habitats we observe the changes in territory usage pattern, in size of individual plots, in rhythm of daily activity that changes the effect of anthropogenic factors, namely disturbance. Birds are an integral part of many ecosystems that quickly responds to the impact of various environmental factors. This is enough plastic group of vertebrate animals that can acquire new adaptation and change in the distribution pattern of anthropogenic territories under the influence of anthropogenic factors under the influence of anthropogenic factors. Birds as a mandatory component of the animal population of the towns involved in the processes of urbanization and synanthropization; but the regularities of bird communities in the human transformed areas are not studied enough and require study that is more detailed. Based on the analysis of literary sources we can talk only about certain commensal trends in corvids, but we cannot make firm conclusions regarding aspects of urbanization and synanthropization in urban and rural populations of Corvidae. Virtually we have no information on the reduction of migration activity, changes in the breeding of the stereotype, the dynamics of the rhythm of life study group of birds on the territory of Ukraine, with varying degrees of urbanization. Therefore, due to the intensification of human transformation of natural communities that lead to fundamental changes in structure of natural ecosystems, there is an urgent need to clarify these issues, whereas Corvidae could be used as a model for the study of bird synanthropization and urbanization.